Peyton Manning : Champion Football Star - Rappoport, Ken. (Berkeley Heights, NJ : Enslow Publishers, 2013)
"Explores the life and career of quarterback Peyton Manning, including his high school and college career, his rise to stardom in the NFL, and his remarkable achievements with the Indianapolis Colts"--Provided by publisher.
Battle of the quarterbacks -- Born to be a quarterback -- Bowling them over -- A frisky Colt -- Super season -- Super day -- Career statistics -- Where to write -- Words to know.
Includes bibliographical references (p. 47) and index.
Keywords: Manning, Peyton -- Juvenile literature; Manning, Peyton; Football players -- Biography -- United States; Quarterbacks (Football) -- Biography -- United States; Football players -- Biography -- United States; Quarterbacks (Football) -- Biography -- United States